Constitutional economics : a primer / Stefan Voigt. - Voigt, Stefan (Cambridge University Press, 2020)
Constitutional political economy has emerged as an indispensable part of political economy. This book offers a concise survey of the questions, methods, and empirical findings central to this topic. What effects - if any - do constitutions have within autocracies? Can small electoral districts help reduce corruption? Does a country's leadership affect the size of its government? Can direct democratic institutions increase politicians' accountability to citizens? Stefan Voigt, a pioneer in the field, explores these questions and more throughout the course of this cutting-edge primer. As the number of courses in constitutional economics continues to grow, this book fills an important gap in the literature. This highly original project maintains curiosity about the questions it generates, identifying potential new areas of research whilst successfully demonstrating the impact constitutional rules have on political economy.